1982
DOI: 10.1161/01.res.50.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Role of renal nerves, angiotensin II, and prostaglandins in the antinatriuretic response to acute hypercapnic acidosis in the dog.

Abstract: Although clinical studies suggest that chronic hypercapnic acidosis may be associated with renal sodium retention, little information is available on the effect of acute hypercapnic acidosis on renal sodium excretion. We, therefore, increased Pco 2 from 23 to 74 nun Hg in anesthetized dogs and observed a marked antinatriuresis as absolute sodium excretion (235 to 60 juEq/min, P < 0.001) and fractional excretion of sodium (4.0 to 1.2%, P < 0.02) decreased significantly. This decrease in sodium excretion occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Several investigators reported that renal blood flow decreased during hypercapnia (STONE et al, 1958;BERSENTES and SIMMONS, 1967;NORMAN et al, 1970;FABER et al, 1976;ANDERSON et a!.,1983) and this decrease was attenuated after renal denervation. Other studies showed that hypercapnia decreased urinary sodium excretion (ANDERSON et al, 1982) and increased renin secretion (Fuii Jand ZEHR, 1975;MORITA, 1976;KURTZ and ZEHR, 1978;STASZEWSKA-BARCZAK, 1978). These observations together with our present results suggest that an increase in RNA during hypercapnia might contribute to maintain arterial blood pressure by counteracting the direct vasodilating effect of hypercapnia and by exerting antinatriuretic and antidiuretic actions.…”
Section: Effectssupporting
confidence: 82%
“…Several investigators reported that renal blood flow decreased during hypercapnia (STONE et al, 1958;BERSENTES and SIMMONS, 1967;NORMAN et al, 1970;FABER et al, 1976;ANDERSON et a!.,1983) and this decrease was attenuated after renal denervation. Other studies showed that hypercapnia decreased urinary sodium excretion (ANDERSON et al, 1982) and increased renin secretion (Fuii Jand ZEHR, 1975;MORITA, 1976;KURTZ and ZEHR, 1978;STASZEWSKA-BARCZAK, 1978). These observations together with our present results suggest that an increase in RNA during hypercapnia might contribute to maintain arterial blood pressure by counteracting the direct vasodilating effect of hypercapnia and by exerting antinatriuretic and antidiuretic actions.…”
Section: Effectssupporting
confidence: 82%
“…Indirect support for this contention has been provided by studies which have demonstrated that a-adrenoceptor antagonists inhibited the angiotensin II-induced increase in active sodium transport in rat kidney cortical slices (Brunton, Parsons & Poat, 1978) and the angiotensin II-induced antinatriuresis in intact rats (Radhi, Chapman & Munday, 1982), implying that angiotensin II exerted its effect indirectly through the release of noradrenaline from sympathetic nerve endings. Two studies in the dog have also shown that captopril or angiotensin II receptor antagonists attenuated the renal nerve-mediated antinatriuresis during hypercapnic acidosis (Anderson, Henrich, Gross & Dillingham, 1982) or shock avoidance (Koepke & Obrist, 1983), in the absence of changes in renal haemodynamics. Together these data would establish that angiotensin II plays an important role in modulating neurotransmission at the level of the renal tubule comparable to that exhibited at neurovascular junctions within the sympathetic nervous system.…”
Section: Low-level Renal Nerve 8timulationmentioning
confidence: 97%
“…Thus, the hemodynamic effects of catecholamines are modulated by a complex interaction with the renin angiotensin and PG systems. Hypercapnic acidosis associated with an increase in PCO 2 from 25 to 70 mm Hg activates the RSNA, and renal denervation studies indicate that the neurally mediated renal vasoconstriction is effectively counteracted, at least in part, by enhanced synthesis of vasodilatory PGs [1735] . Inhibition of the RAS partially attenuates the constrictor effects of RNS during cyclooxygenase inhibition [1096,1733] .…”
Section: Neural Interactions With Paracrine Factorsmentioning
confidence: 99%
“…Afferent nerve endings contain the neuropeptides, CGRP, substance P, and vasoactive intestinal peptide [1764][1765][1766] . Two examples of excitatory renorenal reflexes that are initiated by increased renal afferent nerve traffic and affect renal hemodynamics are neurally-mediated ipsilateral vasoconstriction during increased renal venous pressure and contralateral renal vasoconstriction following a unilateral increase in ureteral pressure [474,1664,1696,1707,1735,1762] . Chemoreceptors sense the electrolyte composition of pelvic fluid, in particular potassium concentration and pH, and also are responsive to renal ischemia.…”
Section: Afferent Renal Nervesmentioning
confidence: 99%